2020
DOI: 10.1098/rsob.200019
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into the powerful mucus-based adhesion of limpets ( Patella vulgata L.)

Abstract: Limpets ( Patella vulgata L.) are renowned for their powerful attachments to rocks on wave-swept seashores. Unlike adult barnacles and mussels, limpets do not adhere permanently; instead, they repeatedly transition between long-term adhesion and locomotive adhesion depending on the tide. Recent studies on the adhesive secretions (bio-adhesives) of marine invertebrates have expanded our knowledge on the composition and function of temporary and permanent bio-adhesives. In comparison, our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 104 publications
1
31
0
Order By: Relevance
“…Cnidarians do not possess brains, however they do produce abundant glycoproteins and, with further analysis of the literature, DMBT1 was found to encode a glycoprotein of unknown function in humans (Madsen, Mollenhauer & Holmskov, 2010). Interestingly, a protein identified in limpet mucus, P-vulgata_10, was also annotated as DMBT1 (Kang et al, 2020). Yet, the three proteins are only superficially similar (Fig.…”
Section: Limitations: Important Considerations For 'Omics-based Bioadhesion Studiesmentioning
confidence: 96%
See 3 more Smart Citations
“…Cnidarians do not possess brains, however they do produce abundant glycoproteins and, with further analysis of the literature, DMBT1 was found to encode a glycoprotein of unknown function in humans (Madsen, Mollenhauer & Holmskov, 2010). Interestingly, a protein identified in limpet mucus, P-vulgata_10, was also annotated as DMBT1 (Kang et al, 2020). Yet, the three proteins are only superficially similar (Fig.…”
Section: Limitations: Important Considerations For 'Omics-based Bioadhesion Studiesmentioning
confidence: 96%
“…7). For example, the putative cohesion proteins Mlig-ap1 (flatworm), Sfp1 (sea star) and P-vulgata_1 (limpet) all contain vWD, EGF, and lectin-binding domains, which are known to mediate protein-protein and proteincarbohydrate interactions (Hennebert et al, 2014;Wunderer et al, 2019;Kang et al, 2020). Conserved blocks of different domains might be indicative of common evolutionary origin.…”
Section: Challenges: How Can Bioadhesion Research Continue To Benefit From 'Omics?mentioning
confidence: 99%
See 2 more Smart Citations
“…They live on seashores and withstand tidal waves, wind and predators by strong adhesion from their pedal sole (adhesion tenacity between 0.1 and up to 1.1 MPa). [ 99 ] In contrast to mussels, limpids secrete different glue depending on their purpose: locomotion or stationary attachment. It was found that the differences between both types of mucus are mostly derived by larger protein and carbohydrate content for the stationary mucus.…”
Section: Solid–water Interfacementioning
confidence: 99%